The influence of activator types on the capacitance value of carbon electrodes from coconut shell - Heri Rahmat Suryadi; Irmawati Amir; Rustan Ruslan; Nur Afrianah; Al Irsyad; Jasruddin Jasruddin; Abdul Haris (Journal of Aceh Physics Society, 2022)
Abstrak. Penelitian ini bertujuan untuk mengetahui karakteristik karbon aktif dalam aplikasi elektroda karbon dari tempurung kelapa serta pengaruh jenis dari aktivator yang digunakan terhadap kapasitansi elektroda karbon dari tempurung kelapa. Karbon yang telah diperoleh dari tempurung kelapa diproses hingga mencapai ukuran 300 mesh. Karbon tersebut kemudian diaktivasi dengan beberapa aktivator seperti HCl, NaOH dan K2CO3 dengan perbandingan 1:1. Karbon yang telah diaktivasi selanjutnya dikeringkan dengan oven kemudian dilakukan pencucian hingga netral. Karbon aktif kemudian dipelet menjadi elektroda dalam tekanan 8 ton lalu selanjutnya dilakukan pengukuran dimensi dan densitas serta pengujian Cyclic Voltametry. Hasil pengukuran dimensi diperoleh nilai densitas dari CSC, AC1, AC2 dan AC3 masing-masing 0,794 g/cm3, 0,610 g/cm3, 0,649 g/cm3 dan 0,731 g/cm3. Selanjutnya hasil pengujian Cyclic Voltametry diperoleh data kapasitansi spesifik, energi spesifik dan daya spesifik. Nilai kapasitansi spesifik dari CSC, AC1, AC2 dan AC3 adalah masing-masing 0,361011 F/g, 0,33898 F/g, 3,38583 F/g dan 4,461538 F/g. Lalu nilai rapat energi dari CSC, AC1, AC2 dan AC3 adalah masing-masing 0,045126 Wh/kg, 0,042373 Wh/kg, 0,423228 Wh/kg dan 0,557692 Wh/kg. Kemudian nilai rapat daya dari CSC, AC1, AC2 dan AC3 adalah masing-masing 0,216606 W/kg, 0,196721 W/kg, 2,186441 W/kg dan 2,676923 W/kg. Abstract. This study aims to determine the characteristics of activated carbon in the application of carbon electrodes from coconut shells and the influence of the type of activator used on the capacitance of carbon electrodes from the coconut shell. The carbon that has been obtained from the coconut shell is processed up to 300 mesh in size. The carbon is then activated with several activators such as HCl, NaOH and K2CO3 with a ratio of 1:1. Activated carbon is then dried in an oven then washed to neutral. Activated carbon is then pelleted into electrodes under a pressure of 8 tons, which is then tested by Cyclic Voltametry. Activated carbon is then pelleting be electrodes under a pressure of 8 tons and then measurements of dimensions densities and done testing by Cyclic Voltammetry. Dimension measurement results obtained density values from CSC, AC1, AC2 and AC3 are 0,794 g/cm3, 0,610 g/cm3, 0,649 g/cm3 dan 0,731 g/cm3 respectively. Furthermore, the results of the Cyclic Voltametry test obtained data on specific capacitance, specific energy and specific power. Specific capacitance values of CSC, AC1, AC2 and AC3 are respectively 0.361011 F/g, 0.33898 F/g, 3.38583 F/g and 4.461538 F/g. Afterwards the energy density values of CSC, AC1, AC2 and AC3 are respectively 0.045126 Wh/kg, 0.042373 Wh/kg, 0.423228 Wh/kg and 0.557692 Wh/kg. Then the power density values of CSC, AC1, AC2 and AC3 are respectively 0.216606 W/kg, 0.203390 W/kg, 2.031496 W/kg and 2.676923 W/kg.